A influência dos podcasts e mídias digitais no processo de ensino-aprendizagem - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study addresses the influence of podcasts and digital media on the teaching learning process, highlighting their expansion as instruments of pedagogical mediation. Transformations in communication methods driven by the internet have modified the relationship between listeners and media content, favoring the use of audio products such as podcasts. These tools, associated with the logic of on-demand consumption and the social media environment, are being adopted in the educational context, especially in approaches such as the flipped classroom, which place the student at the center of learning. The research seeks to understand how the scientific literature discusses the use of podcasts in education, pointing to their pedagogical potential by combining attributes such as accessibility, portability, and flexibility. The structure of the work involves a theoretical review of digital media and teaching learning, a methodological description, an analysis of results, and final considerations focused on reflecting on the educational possibilities of audio media.
The influence of podcasts and digital media on the teaching-learning process
Keywords: Podcasts; Mídias digitais; Ensino-aprendizagem; Inovação pedagógica; Digital media; Teaching and learning; Pedagogical innovation; CIENCIAS SOCIAIS APLICADAS